Management Environmental Language of Usbu' Arabiy MTSN 6 Ponorogo at Pusdiklat Unida Gontor - Saputra, Riski Janu; Anwar, M. Syahrul; Fikri, Naufal (Maharaat: Jurnal Pendidikan Bahasa Arab, 2023)
Bi'ah 'arabiyah is an Arabic-speaking environment, where one interacts with other people and uses the means of communication, namely Arabic. The phenomena found by researchers at MTs N 6 Ponorogo that teaching language in madrasas has several problems, including the lack of students who are able to speak Arabic and learning outside the classroom that is less interesting. This study aims to: describe the management of the Arabic language environment on the Usbu' Arabiy MTsN 06 Ponorogo agenda at the UNIDA Gontor Education and Training Center and describe the requirements and principles for establishing the Usbu' Arabiy Arabic language environment at MTSN 06 Ponorogo at the UNIDA Gontor Education and Training Center. The research methodology used in this research is a qualitative approach with literature studies or literature studies and case studies. The data collection process was carried out using the observation method and interviews with several teachers from the UNIDA Gontor Education and Training Center. Data analysis applied in this research is descriptive analysis. The results of the study stated that the activities at Usbu' Arabi were Giving Mufrodat, Formal Class Learning, Repetition and memorizing vocabulary, Language Skills, Rihlah Lughawiyah, Daily Study, Language Court, and Language Festival and supported by committees and teachers whose Arabic competence was appropriate in create an active and engaging language environment.